Effect of educational intervention on the knowledge of health workers regarding exposures to blood borne pathogens - Ishola, Garba Jamiu Olalekan; Alsaidi, Nahla Abduljaleel (Penerbit Universiti Kebangsaan Malaysia, 2024)
Healthcare workers (HCWs) face a multitude of occupational hazards, including the risk of blood borne infections resulting from sharp instrument injuries and exposure of skin and mucous membranes to contaminated blood and body fluids (BBF). Existing empirical evidence, albeit limited, indicates a deficiency in the knowledge of occupational safety among health workers, consequently raising concerns about their adherence to safety-related practices. Nonetheless, numerous studies have demonstrated that enhanced knowledge regarding safety precautions can mitigate the risk of exposure to diseases transmitted through blood and body fluids. The purpose of this study was to find out the effectiveness of educational intervention in improving knowledge of universal precautions among Health workers about exposures to blood pathogens. Specifically, it examined literature published between 2017 and 2023. This study conducted a literature review on published articles about the effectiveness of educational programs on knowledge of health workers about safety measures against exposure to blood pathogens. There were disparities in baseline knowledge levels among healthcare workers. While some studies indicated poor knowledge pre-intervention, others reported relatively high levels, particularly regarding certain aspects such as injection safety or HIV guidelines. However, educational interventions significantly improved workers' knowledge regarding blood borne pathogens and reduced exposure risks. All studies highlighted the effectiveness of educational interventions in improving healthcare workers' knowledge of blood borne pathogens. Significant increases in knowledge scores were observed post-intervention across various studies, indicating the efficacy of educational programs in enhancing understanding and awareness.